THE FIGHT AGAINST CORRUPTION IS ONE OF THE MOST IMPORTANT ISSUES IN JADIDISH DOCTRINE - Abdivohidov Sunatillo Abdinabievich (Galaxy International Interdisciplinary Research Journal, 2021)
Corruption is one of the main threats to the prosperity of the people, the development of society,the development of the country, the rule of law, human rights, social and economic development.